Anti-corruption laws as a pillar of national security protection: wartime peculiarities - Madryha, Tetiana; Berezovska-Chmil, Olena; Kobets, Yuliia; Bortnikov, Valerii; Panasiuk, Oleksandr (Universidad Hemisferios, 2025)
The analysis focuses on how anti-corruption rules ensure both national security and support it during times of war when corruption endangers stability. Our study checks if existing anti-corruption rules and institution systems help protect national security effectively. The research methods compare different anti-corruption laws, including the Foreign Corrupt Practices Act (FCPA), the PIF Directive (Protection of the European Union's Financial Interests Directive), and the Ukrainian national legislation. This research uses both quantitative Corruption Perception Index (CPI) measurements alongside computer-based systems to spot corruption. Our findings prove that, when governments stay separate from anti-corruption efforts and institutions support political stability combined with economic openness, it is possible to create social unity. Therefore, comparing international frameworks, especially the PIF Directive, against Ukrainian conditions can boost efforts to adapt the Ukrainian anti-corruption policy to its unique requirements. Likewise, digital technologies assist transparency according to research that shows how artificial intelligence (AI) monitoring systems and electronic systems for purchasing items help achieve this goal. On the other hand, corruption during wartime prevents the military from performing effectively while leading to wrong resource usage and losing public support. The analysis shows that nations must develop strong corruption prevention methods in hybrid conflicts to defend their security interests. The results help create anti-corruption policy suggestions for Ukraine that focus on strengthening legislation and digital platforms while preserving autonomy of anti-corruption institutions. Our findings help both experts and officials of public administration improve governance and security for both academics and policy makers. These findings indicate that researchers should inspect the long-term success of anti-corruption actions and their ability to strengthen national resistance against external danger.